Optimal short‐circuit current control of the grid‐forming converter during grid fault condition - Chang Liu; Xu Cai; Rui Li; Renxin Yang (IET Renewable Power Generation, 2021)
Abstract A considerable amount of rotating synchronous machines are being replaced by the increasing capacity of converter‐based resources, which has stimulated a demand for grid‐forming converters (GFCs) for grid supporting. The inertia and frequency responses of GFC are remarkably similar to those of synchronous generator (SG), but the inadequate capability of sourcing short‐circuit current of GFCs during grid fault can lead to several serious consequences. The low short‐circuit current level fails to trigger protection relays and cannot provide sustained voltage support during the fault or more effectively support the recovery of voltage after fault clearance. The short‐term overcurrent capability of GFC can be promoted either from the point of view of the power devices or from the topology of it. The overcurrent capability of converter is hard‐earned, so full use of it should be made. This paper proposes an optimal control strategy of short‐circuit current of GFC, which can enable the GFC to source the short‐circuit current with an optimal angle within the allowable magnitude. A detailed simulation model of the proposed method here is set up in PSCAD/EMTDC. The simulation results show that the proposed method can achieve better voltage supporting results compared with the traditional reactive support control.